"You Have to Approach Us Right": A Qualitative Framework Analysis for Recruiting African Americans Into mHealth Research. (October 2017) - James, Delores C. S.; Harville, Cedric; Efunbumi, Orisatalabi; Babazadeh, Ida; Ali, Sheriza
Background . Despite the high ownership of smartphones, African Americans (AAs) remain underrepresented in health research and specifically mobile health (mHealth) research. This may be due to ineffective recruitment efforts. Purpose. To explore strategies for recruiting AAs into mHealth research and examine how these strategies may vary by gender and age-group. Method. Twenty triad focus groups ( n = 60) were conducted with AA males ( n = 9 groups) and females ( n = 11 groups). The framework method was used to manage, organize, synthesize, and analyze data themes by gender and age-group (18-29, 30-50, 51+). Results. Most participants owned smartphones (71%) and were willing to participate in mHealth research (62%). The participants' narrative revealed the tension between mistrust of researchers and the excitement of participating in technology-based research. Both genders and all age-groups can be reached via word-of-mouth because it is "the best advertisement." Personal contact must precede traditional and electronic recruitment strategies because "we have to know you." Churches are excellent places for recruitment because they are "trustworthy" and have a "repeat audience." Facebook may be effective for both genders and all age-groups because "everybody is on Facebook" and it can "reach more people than text and e-mail." Beauty/barber shops may be limited in reaching both genders and age-groups, but especially young women who style their own hair natural, and young men who wear braids and dreadlocks. Personal contact must precede traditional and electronic recruitment strategies because "we have to know you." Conclusion. A tailored, multipronged strategy that combines traditional recruitment methods with texting, e-mail, and social media may be effective in recruiting AA adults into mHealth research.